Strengthening Digital Data Governance for Poverty Alleviation and Community Economic Empowerment in Lebak Regency - Roy Tumpal Pakpahan; Rizal Bahtiar; Saripan Saripan (Journal of Public Policy, Governance and Local Government, 2026)
This study examines how digital data governance supports poverty alleviation and community economic empowerment in Lebak Regency, with particular attention to the use of Targeting Data for the Acceleration of Extreme Poverty Elimination (P3KE). A descriptive qualitative approach was employed, using interviews, direct observation, and document-based evidence, while data were analyzed interactively through reduction, display, and conclusion drawing. The analytical framework adopts Suharto’s community empowerment dimensions of enabling, empowering, and protecting. The findings show that digital data provides a strategic foundation for identifying poor households, mapping locations, defining intervention priorities, and connecting vulnerable groups with economic empowerment programs. However, the effectiveness of P3KE and other government databases is constrained by discrepancies between administrative records and actual field conditions, limited data integration and updating, uneven human resource capacity, inadequate technological infrastructure, and weak internet connectivity. These limitations can reduce targeting accuracy and weaken the accountability of poverty alleviation programs. The study therefore emphasizes the need for routine field validation, interoperable data management, continuous updating, stronger inter-organizational coordination, improved staff capacity, and adequate digital infrastructure. Effective data governance should also link poverty identification with access to capital, technology, information, markets, training, and public services. The study concludes that digitalization will contribute to inclusive and sustainable poverty reduction only when data quality, institutional capacity, and community empowerment are integrated within an evidence-based governance system